Trends in physical fitness among polish children and adolescents - Baj-Korpak, Joanna; Zaworski, Kamil; Wochna, Marek; Chmara, Sebastian; Stelmach, Marian J. (Frontiers in Public Health, 2025)
BackgroundHuman health, with physical fitness as one of its key indicators, is characterized by a dynamic nature. Therefore, monitoring motor abilities and the factors that influence them becomes particularly important. Recent studies on physical fitness trends among children and adolescents indicate a declining tendency, with a noticeable decrease in physical performance. Maintaining an optimal level of physical fitness in young individuals requires support not only from parents. Hence, health promotion policies should focus on fostering health-related physical fitness from early childhood. The aim of the current study was to determine physical fitness trends among Polish children and adolescents participating in the nationwide program “Athletics for All!” (AFA). An attempt was made to answer the question of whether the implementation of programs promoting physical activity among youth (as exemplified by the AFA program) has an impact on improving physical fitness and body build indicators as its markers.MethodsPhysical fitness was assessed in a group of 54,049 young individuals, including 31,789 girls and 22,260 boys, over eight consecutive years of the AFA program’s implementation. The assessment was conducted using the OSF test, developed specifically for the AFA program, which includes a 3×10 m shuttle run, standing broad jump, 1 kg medicine ball throw, and a 4-min run. Statistical analyses were performed separately for each gender, assuming a significance level of alpha = 0.05. It was verified whether there were significant differences in the means between the groups distinguished based on the year of the study.ResultsThe study results indicate that the implementation of the AFA program promoting physical activity among Polish youth has a positive impact on the improvement of physical fitness and body build parameters. Statistically significant differences were found in the mean values of measurements taken over the course of eight consecutive years. The results of multiple comparisons between the mean values of all the analyzed variables in different years revealed significant differences in most of the comparisons.ConclusionThe level of physical fitness among participants of the AFA program remained relatively stable over nearly a decade, which, in an era dominated by a sedentary lifestyle among modern youth, confirms the validity of implementing physical activity promotion programs (including the AFA program).